ETIOPATHOGENESIS OF ATHEROSCLEROSIS AND THERAPEUTIC TRIAL WITH SADUSANA CHURNA - Ekka Ranjita; Sharma Surendra Kumar (International Journal of Applied Ayurved Research, 2015)
A research work was done to evaluate the therapeutic effect of the drug Sadusana churna in patients of atherosclerosis. As per inclusion criteria 30 patients of atherosclerosis were selected for the therapeutic trial. The drug Sadusana churna was prepared as per the classical reference and all patients were advised to take 3gm of Sadusana churna twice daily after food with leuk warm water for three months. After 3 months of trial the effect of the drug was found very significant. Also no adverse effects were reported by patients during the study. Hence it can be concluded that Sadusana churna is useful in treatment of Atherosclerosis with relation to lifestyle disorder.